Aplicación del branding político en las estrategias de comunicación de los candidatos presidenciales de los partidos Juntos por el Perú y Renovación Popular en la campaña electoral 2021 - Galindo, Alvaro (2022)
This study examines the strategies used through branding by presidential candidates in the context of the presidential election campaign in 2021 to strengthen their presence in peruvian population. The aim of this study is to analyze the application of the communication strategies of the presidential candidates political branding of the political parties: Juntos por el Perú and Renovación Popular during the first round of elections and its impact on young college students perception, through and analysis of political speech and graphic material on Instagram accounts of the political figures mentioned. The study reveals that said application it’s shown on the particular use of verbal and not verbal communication portrayed in the political speech and graphic material that consolidate their brand and character, which, although can be shown through positive perceptions of the young college students, there is still distrust to a certain extent when it comes to authenticity of the political candidates and the way they address the audiences.